Tanggung Jawab Guru Dalam Pengembangan Kompetensi Profesional - Marjuni, A. (Inspiratif Pendidikan, 2016)
The teachers principles and responsibilities in competence development of professional teachers are; 1) having commitments to the quality of planning, process, and results achieved in education; 2) having a good moral to be a role model for students; 3) having a sincere intention for God in educating; and 4) having human relations with the various involved parties in improving lesson on learners. So that competence in this case can be interpreted as an ability that should be had by the teachers in order to realize their performance appropriately and effectively. Professional teachers always master the science substance related to their field of study and master the structures and methods of science.